Analisis Fungsi dan Tahapan Manajemen Perubahan dalam Pendidikan Islam Transformatif - Fara Fariha Rodliyana; Binti Maunah; Asrop Safi’i (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Changes in Islamic education in the modern era have become increasingly crucial in line with technological advancements, social dynamics, and the growing needs of Muslim communities. Islamic educational institutions are now expected not only to transmit religious teachings but also to nurture learners who are religiously grounded, adaptable, creative, and capable of facing global challenges. Therefore, change management plays a vital role in ensuring that the transformation process proceeds in a structured, systematic manner while remaining rooted in Islamic values. This study examines key management functions—planning, organizing, actuating, and controlling—as well as stages of change developed in models such as those of Lewin and Kotter as the foundation for implementing transformative Islamic education. This research employs a literature study method with a descriptive qualitative approach by analyzing books, scholarly articles, relevant studies, and Islamic education policy documents. The findings indicate that the success of Islamic education transformation greatly depends on the synergy of all management functions. Planning helps formulate the direction of change; organizing ensures that institutional structures operate effectively; actuating requires inspirational leadership and a collaborative culture; while controlling ensures that the process remains aligned with established goals. The stages of change also emphasize the importance of building readiness, implementing strategic steps, and reinforcing new cultural patterns. Overall, change management in Islamic education involves not only technical adjustments but also the strengthening of values, character, and spirituality.